Vacuum Ultraviolet Source - U. Feldman; M. Swartz; Leonard Cohen (1967)
A low inductance three-electrode spark source for the vacuum ultraviolet fed by a 20-kV, 13-μF capacitor is described. Its main feature is its ability to generate spectra of very high degrees of ionization. A 6-kV spark produces spectra of CV and CVI as well as FeXVI, while a 17–18-kV spark yields FeXVIII, AlXII, and AlXIII.